A STUDY ON FINANCIAL PERFORMANCE OF ANDHRA BANK THROUGH CAMEL APPROACH - BANANA, Dr. KRISHNA; CHEPURI, V.RAMA KRISHNA RAO (IJRDO - Journal of Business Management, 2017)
The growth of an economy is widely dependent upon deployment as well as optimum utilization of resources and most importantly operational effectiveness of the various sectors, of which banking sector plays a very important role. Performance evaluation of the banking sector is an effective measure and indicator to check the reliability of economic activities of an economy. CAMEL approach is an effective tool to assess the relative financial strength of a bank and to suggest necessary measures to overcome weaknesses of a bank. The present study focuses on the evaluation of the performance of Andhra Bank with CAMEL model. The study adopts an analytical and descriptive research design. The data for a period of 10 years i.e., 2007-08 to 2016-17 have been collected from the annual reports of the bank. Sixteen variables as supported by the existing literature related to CAMEL model are used in the study. The study identified that the bank is maintaining consistency in capital, deep dwindle in the quality of the asset, the productivity and profit per employee reduced, continuous decrease in earnings and liquidity. The growth of deposits, net profit and number of branches are measured through Compound Annual Growth Rate. The net profit presented a negative cumulative growth rate of -11.28%. Hence it is advised to improve profit by minimizing expenditure.